Treatment of recurrent aneurysms using the Woven EndoBridge (WEB): anatomical and clinical results. (20th October 2017) - Gawlitza, Matthias; Soize, Sebastien; Januel, Anne-Christine; Mihalea, Cristian; Metaxas, Georgios-Emmanouil; Cognard, Christophe; Pierot, Laurent
Abstract : Background: The safety and efficacy of the Woven EndoBridge (WEB) for the treatment of naïve intracranial aneurysms has been confirmed. Purpose: To analyze the safety and efficacy of the WEB in the treatment of recurrent aneurysms. Methods: Anatomical and clinical results in consecutive patients with a recurrent aneurysm, who were treated using the WEB device in two French neurointerventional centers, were evaluated. Results: Seventeen patients with 17 aneurysms were included. Treatment was feasible in 16 patients. In seven patients (41.2%), ancillary devices were used. Permanent morbidity due to a thromboembolic complication occurred in one patient (5.9%). There was no mortality. Follow-up angiographic studies were available for 15 patients after a mean of 12.1±6.1 months. Rates of complete occlusion, neck remnant, and aneurysm remnant were 33.3%, 40.0%, and 26.7%, respectively. Conclusions: Treatment of recurrent aneurysms using the WEB device may be reasonably safe and effective.